2020
DOI: 10.1128/mra.00673-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Reveals the Genome Sequence of Pea Early Browning Virus from a 29-Year-Old Faba Bean Sample

Abstract: ABSTRACT Pea early browning virus (PEBV) is transmitted by soil-inhabiting trichodorid nematodes and via seeds. The transcriptome sequencing method, followed by de novo assembly, revealed the PEBV Libyan isolate LyV66-91 genome. Its RNA1 resembled that of UK isolate SP5 with 93.91% nucleotide identity, and its RNA2 had 63.32% nucleotide identity to that of Dutch isolate E116.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Van der Merwe et al (2023) extend this, advocating for the storage of maternal lines to increase potential conservation applications. The utility of genetic analyses was demonstrated in biosecurity screening of imported crop seeds for virus detection (Maina et al 2021).…”
Section: Seed Sourcing and End-usementioning
confidence: 99%
“…Van der Merwe et al (2023) extend this, advocating for the storage of maternal lines to increase potential conservation applications. The utility of genetic analyses was demonstrated in biosecurity screening of imported crop seeds for virus detection (Maina et al 2021).…”
Section: Seed Sourcing and End-usementioning
confidence: 99%
“…It is found in Africa, Asia, Europe, and the Middle East, where it causes severe damage in pulses ( 1 – 3 ) and constitutes a threat to crop improvement programs ( 4 ). BBMV is a quarantinable pathogen in Australia; consequently, it is mandatory for the imported seeds to be screened within post-entry quarantine (PEQ) ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…Primers were designed from the newly generated BBMV RNA3 coat protein (CP) region, targeting 250 to 500 bp, and amplified the expected amplicon band size. Annotation of the BBMV genome ( 5 ) revealed that both RNA1 and RNA2 encoded open reading frames 1a and 2a, typical of the genus Bromovirus , to which BBMV belongs ( 13 ). Further, RNA3 encoded the CP gene, which is required for virus systemic movement and associated with cell-to-cell spread ( 14 ).…”
Section: Announcementmentioning
confidence: 99%
“… a = Genome sequence of PEBV as reported [ 29 ], b = BYMV as reported [ 30 ], 13C and 14C = new PSbMV and CMV genome sequences generated from this study. c = Average coverage depth across the genome (x) times.…”
Section: Figurementioning
confidence: 99%
“…Supplementary Table S1: Summary of concentrations in ng/uL RNA templates used for RNA-Seq, cDNA amount used for PCR and mPCR and finally the library template used for TG-Seq. Supplementary Table S2: Summary of RNA-Seq paired-end data of the four samples LY-2 = Genome sequence of PEBV as reported [ 29 ], 14BY = BYMV infected sequenced sample as reported in [ 30 ], 13C and 14C = new PSbMV and CMV sequences generated from this study. Percentage of viral reads = number of reads that mapped back to the viral genome of interest.…”
mentioning
confidence: 99%